Application of Hash Sha-256 Algorithm in Website-Based Sales Software Engineering - Khasanah, Fauziah Nikmatul (Bright Publisher, 2022)
Rapid technological developments can spur changes in the cycle of human activities, one of which is software engineering activities that continue to develop in accordance with technological developments, the development of software engineering activities is also developing methods of data security to withstand attacks from irresponsible parties. answer. This research was conducted to analyze the performance and robustness of the sha-256 data security method with ciphertext customization. The steps that the researchers took in conducting the analysis were collecting theory and case examples, designing programs, implementing programs, testing and saving the results. Based on this process, it can be concluded that ciphertext customization on sha-256 is needed to strengthen security and resistance to attacks from irresponsible parties, besides that the performance of sha-256 calculations with customization on ciphertext and without ciphertext is not too much different where only 65 ms difference based on the results of performance testing that researchers did.